Two new reports of armored scale insects (Hemiptera: Diaspididae) infesting Ficus pumila L. (Moraceae) in the Brazilian Midwest - Castro, Marcelo T.; Montalvão, Sandro C. L.; Wolff , Vera R. S. (Entomological Communications, 2025)
Ficus pumila L. (Moraceae) is a species frequently used as an ornamental plant in many Brazilian regions. Until now, 22 species of scale insects (Hemiptera: Coccomorpha) have been reported infesting F. pumila around the world. In this work, two new reports of armored scale insects (Hemiptera: Diaspididae) associated with F. pumila in the Brazilian Midwest are presented: Pseudaonidia trilobitiformis (Green, 1896), infesting leaves, and Hemiberlesia lataniae (Signoret, 1869), infesting fruits, both in the same plant located in the Federal District, Brazil. Studies with scale insects in Central Brazil must be stimulated to catalogue and expand the knowledge about new interactions, occurrence, and possible new species of Cerrado biome.